Regional and Municipal Models of Social Policy in Secondary Education (Part 1) - Yana Roshchina; Oksana Chernenko (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
The object of the study is regional and municipal models of education policy. The newly legislated Law on the General Principles of Organization of Local Self-Government in the Russian Federation requires the reorganization of financing of the education system; this is what makes the present study relevant. The authors use empirical data collected in 4 Russian regions (the Yaroslavl, Tver, Samara regions, and the Chuvash Republic). Detailed interviews with a representative of the Education Department and from 4 to 6 managers of municipal education departments were conducted in each region. In addition, from 5 to 6 secondary school managers in each municipal district also filled in a questionnaire. The analysis of the data showed the existence of 3 models of education policy in the regions: a liberal policy, a social policy, and a centralized policy. They are characterized by different degrees of reliance on economic and administrative mechanisms.